PENYULUHAN MANFAAT KONSUMSI IKAN DI SMA NEGERI 1 SAMBAS - hesti; Maryono; Merdekawati, Dewi; Ningsih, Lutfi Eka Septi; Rosalinda; Sardi; Kurniadi, Deki; Saputra, Miko; Gunawan, Eko; Hanavi, M Ilham (PT. Gelora Cipta Nusantara, 2024)
In order for children to grow and develop properly, they need proper nutrition. Nutritional deficiencies can affect a person's learning ability and cognitive development. Because it is the most important need to have. For children aged six to twelve, fish protein is an important source of nutrients. However, according to Riskesdas in 2013, 30.7% of children this age are stunted, 18.4% are short, and 12.3% are very short. Fish contains omega-3 fatty acids. when compared to beef, chicken, or other types of meat. To encourage children to eat fish, more information should be provided about fish nutrition and its benefits for overall health. The nutritional role of fish in brain development and intelligence should be enhanced. On November 20, 2023, in Sambas District, Sambas Regency, students of SMA Negeri 1 Sambas received counseling on the importance of eating fish. Students should better understand the importance of eating fish, that is the purpose of this counseling.